Integrating the Women, Peace, and Security Framework into Gender-Inclusive Disaster Management in Indonesia - Rahmadhani, Tasya; Susandi, Armi; Heridadi, Heridadi (Darul Yasin Al Sys, 2025)
This study investigates the integration of the Women, Peace, and Security (WPS) framework into gender-inclusive disaster management in Indonesia. Employing a descriptive qualitative approach grounded in document analysis, it examines academic literature, policy documents, and institutional reports to trace the development, implementation, and impact of WPS principles within Indonesia’s disaster governance landscape. The findings reveal a paradigm shift in which women are increasingly recognized not solely as vulnerable populations, but as active leaders and decision-makers in disaster preparedness, response, and recovery efforts. Initiatives such as Desa Tangguh Bencana and Srikandi Tangguh Bencana exemplify the successful localization of the WPS agenda, fostering inclusive community resilience and addressing gender-specific vulnerabilities. The institutionalization of WPS in Indonesia is further supported by frameworks like the National Action Plan for the Protection and Empowerment of Women and Children in Social Conflicts (RAN P3AKS) and Indonesia’s engagement with UN Security Council Resolution 2538, which advocates for women’s roles in peacekeeping and disaster risk reduction. These advancements signify a broader transformation in disaster governance, where gender mainstreaming is recognized as a critical component of national resilience and security. The study concludes that meaningful female participation is essential for building equitable, adaptive, and sustainable disaster management systems in Indonesia.